The Impact of Changing Writing Task Word Limits on Written Performance - Szabó, Gábor (Working Papers in Language Pedagogy, 2020)
This paper investigates whether changing word limits in writing tasks has any measurable impact on the qualities of candidate performances in the framework of language examination tasks. In order to examine the effects of planned modifications in the length of writing tasks in ECL language examinations, a study was conducted to analyze the properties of exam performances of differing lengths. In order to acquire objective measures of the text characteristics, the Coh-Metrix TERA platform and the Coh-Metrix L2 readability index were utilized. First, texts of differing lengths were analyzed, and next the text characteristics were checked for significant differences. The results of the analyses indicated that the change in word limits did not result in significant changes in any of the text properties. Thus, the modifications in the examination would not result in any undesirable consequences concerning the standards, construct, or validity of the exam.